SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0198
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Turbulence and Fuel-Air Mixing within a Scavenged Pre-Chamber Using RANS and LES

Abstract: 20XX-01-XXXX Numerical study of turbulence and fuel-air mixing within a scavenged pre-chamber using RANS and LES Author, co-author (Do NOT enter this information. It will be pulled from participant tab in MyTechZone)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The typical swirling flow of the leaner incoming mixture is visible at 2 and 3 ms, where the colder region is penetrating onto the prechamber in the near-wall region. This swirling flow pattern has been described in detail in [30]. RANS simulation results are qualitatively similar to LES, apart from the smoothness of the flame front.…”
Section: /16/2018supporting
confidence: 60%
See 4 more Smart Citations
“…The typical swirling flow of the leaner incoming mixture is visible at 2 and 3 ms, where the colder region is penetrating onto the prechamber in the near-wall region. This swirling flow pattern has been described in detail in [30]. RANS simulation results are qualitatively similar to LES, apart from the smoothness of the flame front.…”
Section: /16/2018supporting
confidence: 60%
“…LES simulations have been performed on a mesh with a homogeneous cell size within the pre-chamber and the initial 10 mm of the jets in the main chamber of 0.125 mm, and a cell size in the rest of the main chamber of 0.25 mm, leading to approximately 8 million cells at top dead center. The mesh in the pre-chamber is the same as in our previous non-reactive study reported in [30].…”
Section: /16/2018mentioning
confidence: 99%
See 3 more Smart Citations